Crude Nickel Export Moratorium Policy: Implications for Indonesia's Economy and International Trade Relations - Smarayova, Hildita (Balobe Law Journal, 2025)
Introduction: This article discusses the legal and economic implications of Indonesia's raw nickel ore export moratorium policy, implemented through Ministerial Regulation Number 11/2019. The focus includes the dynamics of industrial downstreaming, value-added enhancement, and the international trade dispute with the European Union at the WTO.Purposes of the Research: The study aims to evaluate the policy's effectiveness in supporting sustainable economic development while addressing legal and diplomatic challenges.Methods of the Research: Using a normative-juridical approach and prescriptive analysis of national regulations, WTO documents, and sectoral economic data.Results of the Research: The findings show that while the policy has significantly boosted economic value and industrial growth, it has also led to legal controversies concerning global free trade principles. The article suggests strengthening both domestic and international legal instruments to support natural resource sovereignty and the formulation of sustainable trade policy.